93 Innovating in children's urgent care. (3rd November 2019) - Mathai, Mathew; Basu, Reena
Abstract : Aim: The number of emergency department attendances by children and young (CYP) is on the rise. However, 90% of medical patients are discharged after initial assessment. The Ambulatory Care Experience (ACE) service is a new model for urgent care for CYP. The primary aim of the team is to provide child and family centred quality acute care at the right time and in the right place, ideally at home. The service provides an alternative to a hospital referral or admission for CYP. ACE Intervention Paediatric consultants take clinical responsibility from point of referral. Subsequently, CYP receive up to 5 days of home observation, delivered by a specially trained band 6 nurse. Development of the service has required a system wide, shared ambulatory care vision. It was designed with families by a multidisciplinary team including doctors, nurses, educators and managers. Best available evidence, national guidance and local clinical agreement were used to design and implement the service. In order to deliver the service a bespoke training package for nurses was developed which included the development of robust governance processes covering clinical and non–clinical interactions. Four separate work–streams are led and managed to deliver the service: implementation, training and competence, pathways and clinical governance. Results: Dec 2017- June 2019 83% of patients referred to the service have been managed entirely in the community. There has been 100% positive feedback and no adverse events. Conclusion: ACE is the result of system wide collaboration. The service provides specialist CYP and family centered acute care at home, consistent with the NHS Long Term Plan. It has been designed for adaptation and replication across the NHS. It is a good example of the healthcare leadership model and an innovative way of working, ensuring we can cater for the healthcare needs of our current and future population.